Detection of “Candidatus Helicobacter suis” in Gastric Samples of Pigs by PCR: Comparison with Other Invasive Diagnostic Techniques - De Groote, D. (American Society for Microbiology, 2000)
Recently, a new 16S ribosomal DNA-based PCR assay was developed for the specific detection of “Candidatus Helicobacter suis” (former “Gastrospirillum suis”) in porcine gastric samples. In the present study, this PCR assay was compared to three other invasive diagnostic methods (rapid urease test, immunohistochemistry, histologic analysis by Giemsa staining). Antral stomach samples from 200 slaughterhouse pigs from Belgium and The Netherlands were examined. Bacterial presence was determined in 77% (154 of 200) of the samples by PCR in combination with Southern blot hybridization, 56% (111 of 200) of the samples by immunohistochemistry, 61% (122 of 200) of the samples by urease testing (20 h postinoculation [p.i.]), 36% (71 of 200) of the samples by urease testing (3 h p.i.), and 33% (65 of 200) of the samples by Giemsa staining. The intrinsic specificity of the PCR assay was assessed by Southern blot analysis with an “Candidatus H. suis”-specific probe and sequencing of PCR products. Interassay sensitivity and specificity values were assessed for each test by pairwise comparisons between tests. Agreement between tests was evaluated by calculating Cohen's kappa coefficient. From that analysis, the PCR assay was considered the most reliable benchmark. Microscopic detection of immunohistochemically labeled or Giemsa-stained “Candidatus H. suis” cells in stomach sections proved to be highly specific (100%) but relatively insensitive (72 and 42%, respectively) compared to the PCR assay. A longer incubation time of the urease test improved its sensitivity considerably (74 versus 55%) but was accompanied by a loss of specificity (72 versus 93%). In conclusion, we found the “Candidatus H. suis”-specific PCR assay to be a sensitive and reliable diagnostic method for the detection of “Candidatus H. suis” in the stomachs of pigs and could prove to be a valuable tool for further epidemiological studies both for “Candidatus H. suis”- and for “Helicobacter heilmannii” type 1-related research.